Properties of kenaf fiber-reinforced elastomer composites. - Salit, Mohd Sapuan; EI-Shekeil, Y. A. (2012)
In this study, kenaf short fibers were mixed with thermoplastic polyurethane to form composites in the internal mixer. Testing specimens were prepared by compression molding. At the preparation stage the behavior of the composite was studied under different parameters in the internal mixer. The best results were taken forward to the second stage to study the behavior of the composite under different fiber size. The main criterion in understanding the behavior of the composite was the tensile testing.